Environmental predictors of woody plant encroachment in calcareous fens are modified by biotic and abiotic land‐use legacies. Issue 2 (20th December 2015) - Bart, David; Davenport, Tara; Yantes, Austin
Summary: Woody plant encroachment in grasslands is a world‐wide concern. Assertions that abiotic stress reduction facilitates encroachment are not universally supported. To devise restoration and management strategies, the ability of stress reduction, in the context of co‐occurring biotic land‐use legacies, needs to be assessed to predict shrub cover. We determined whether legacy‐induced reduction in Carex stricta (a potential facilitator of shrub encroachment and attractor of animal dispersers) and an increase in herbaceous invaders (potential competitors) altered the ability of stress reduction to predict woody plant cover in ploughed and never‐ploughed plots within 11 Wisconsin (USA) calcareous fens. We hypothesized that drier conditions (low saturation stress) and higher nutrient availability associated with ploughing would be associated with high woody plant cover; that higher cover of herbaceous invaders associated with ploughing would predict low woody plant cover, and C. stricta cover predicts high woody plant cover in saturated, never‐ploughed plots. Restricted maximum‐likelihood (REML) multiple regression was used to determine the importance of interactions among ploughing, saturation, nutrients and the two biotic legacies in predicting woody richness and cover, as well as cover by dispersal syndromes and individual species. Unexpectedly, encroachment by animal‐dispersed species was higher in never‐ploughed plots, while wind‐dispersed species had no relationship with ploughing. Animal‐dispersed species cover decreased with saturation stress in never‐ploughed plots, only. Carex cover was associated with increased encroachment by animal‐dispersed species, mainly in never‐ploughed highly saturated plots. Herbaceous‐invasive cover was associated with decreased encroachment. Wind‐dispersed species cover declined with increasing saturation stress, with responses varying among species. Synthesis and applications . The results suggest that the impacts of stress reduction on encroachment are not uniform and are modified by biotic legacies. We suggest that impacts of restoring stressful abiotic conditions on encroachment may not be known until the impacts on competitors and facilitators are understood. Abstract : The results suggest that the impacts of stress reduction on encroachment are not uniform and are modified by biotic legacies. We suggest that impacts of restoring stressful abiotic conditions on encroachment may not be known until the impacts on competitors and facilitators are understood.